Women, work and health between the nineteenth and twentieth centuries from a national and international perspective - Salerno, Silvana (La Medicina del Lavoro, 2014)
Background: A few years after a series of meetings of Italian scientists were convened prior to the unification of Italy, the first women qualified in medicine and other dedicated women participated in founding a movement for the improvement of living and working conditions of women and children in Italy. Objectives: analysis of Italian women’s contributions in the proceedings of the International Council of Women Congresses and their impact on increasing the number of women’s occupational health studies presented at the fourth National Congress on Occupational Diseases held in Rome in 1914. Methods: Analysis of the proceedings of the International Council of Women Congresses (Washington, Chicago, London), and of the Women’s National Council and other documents so as to obtain a picture of Italian women’s working conditions at that time. Results: Women and children worked an excessive number of hours per day, were underpaid, and had a legal status of inferiority. The main work sectors were sewing, embroidery, lace making, ironing, cooking, washing, dressmaking, millinery, fashion design, typing, weaving, artificial flowers, etc. The same sort of work was available to Italian women who emigrated to the United States of America. The success achieved by the women’s movement is shown in the paper presented by Irene de Bonis “Occupational diseases among women” and published in the proceedings of the fourth National Congress on Occupational Diseases held in Rome, 9-14 June 1914. Conclusions: The article outlines the main features of the women’s movement at the turn of the twentieth century, focussing on their publications describing Italian women’s working conditions, considered in an international context. The movement’s engagement in the promotion of women’s occupational health at international and national level was successful but the First World War was to transform this achievement into the women’s peace movement.